2021
DOI: 10.1088/1361-6463/abd8bc
|View full text |Cite
|
Sign up to set email alerts
|

The influence of a nickelic interlayer on spin transport efficiency at a YIG/Pt interface

Abstract: Interfacial spin transport efficiency was studied in a yttrium iron garnet (YIG)/Pt spin-pumping system with different nickelic interlayers. It was found that the magnitude of the spin-pumping signals is sensitive to the chemical composition and crystalline orientation of the nickelic interlayers. As shown by the results obtained, a 2 nm thick metallic Ni interlayer enhances the spin-pumping signal, making it several times larger than that found for a YIG/Pt control sample. The spin-pumping signal around room … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
2
0
1
Order By: Relevance
“…[12][13][14] Some studies have recently shown that the spin-current-induced phenomena are enlarged by inserting an antiferromagnetic (AFM) insulator such as NiO and CoO between the FM and HM layers, and concluded that it is due to the enhancement of the spin current transmittance. [15][16][17][18][19][20] In other reports, however, a decrease in the spin-current-induced phenomena has been observed when the AFM insulator is inserted [21][22][23] and thus, the influence of AFM insertion on the SOT remains unclear.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…[12][13][14] Some studies have recently shown that the spin-current-induced phenomena are enlarged by inserting an antiferromagnetic (AFM) insulator such as NiO and CoO between the FM and HM layers, and concluded that it is due to the enhancement of the spin current transmittance. [15][16][17][18][19][20] In other reports, however, a decrease in the spin-current-induced phenomena has been observed when the AFM insulator is inserted [21][22][23] and thus, the influence of AFM insertion on the SOT remains unclear.…”
mentioning
confidence: 94%
“…In a previous study, it was reported that the spin current transmittance was enhanced more by inserting a highly textured fcc(111) NiO layer than by inserting a polycrystalline NiO layer. 20) Thus, one possible reason is the difference in the degree of crystallization of the NiO layer. To test this hypothesis, XRD measurements were performed in the Al 2 O 3 sub./Pt (3 nm)/NiO(10 nm) and Si/SiO x sub./Ta(2 nm)/Pt(3 nm)/NiO (10 nm) structures (labeled as samples A and B, respectively).…”
mentioning
confidence: 99%
“…自旋电子学是以电子的量子自由度自旋为核心对象的研究领域,以自旋为信 息或能量载体的器件研制是自旋电子学的核心研究课题之一 [1][2][3][4] 。 与传统的基于电 荷的电子器件相比,自旋电子器件具有非易失、高速度和低热损等特点,使其有 望成为下一代电子学器件的发展方向。自旋流的产生、输运及检测是自旋电子器 件及其相关研发的基本问题 [5][6][7][8][9][10] 。其中,由于自旋流与传输介质之间具有复杂的 相互作用,导致自旋流输运相关现象长期成为自旋流研究的难点及热点 [11][12][13][14][15] 。不 同的材料及界面状态对自旋流传输影响的研究对开发新型自旋电子学器件具有 重要意义。 正如诺贝尔物理学奖得主Herbert Kroemer的名言 [16] "界面即器件"所述,在 现代电子器件中界面对其功能和性能的主导作用毋庸置疑,对自旋电子器件亦然。 针对自旋流传输现象,金属与金属界面处发生的自旋流反射、损耗和透射现象(图 1(a))已被大量研究。Kurt [17] 等在分析Cu/Pt与Cu/Pd界面的自旋输运时,观察到自 旋损耗导致的自旋流不连续现象。Nguyen [18] 等发现在Co/Pt界面处具有较大的自 旋翻转系数,暗示了自旋极化电流在铁磁层和铂金属层界面处存在无法忽视的耗 散。Rojas-Sánchez [19,20] 成正比 [26,27] [29] )情况下的逆 为进一步分析 YIG/Ni/Pt 三层和 YIG/Ni 双层器件中 Ni 层及 Pt 层分别对逆自 旋霍尔电流 I ISHE 的贡献, 我们首先基于自旋泵浦理论建立以下的等效电路模型 [24,30] 。对于 YIG/Ni 双层器件而言:…”
unclassified